1977
DOI: 10.1159/000222082
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin in a Traumatological Department

Abstract: Fosfomycin has been used in the treatment of 99 patients suffering from varying kinds of osseous processes and divided into 2 groups, one of 60 patients who were not operated on, and another of 39 who were operated. A treatment only with fosfomycin was tried initially by intravenous infusion (8–16 g/day during 2–4 days), then by the intramuscular route (2–8 g/day during 2–6 days) and finishing with treatment by the oral route (2–4 g/day during 2–6 days). The results have been excellent, all cases progressing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…in this analysis) were treated with fosfomycin for osteomyelitis (acute or chronic, hematogenous, vertebral, post-traumatic, post-operative or in the presence of diabetic foot infectionlimb threatening osteomyelitis). Arthritis, pyogenic discitis, septic pseudoarthrosis, internal fixation infection and periprosthetic joint infections were some of the other indications for which intravenous fosfomycin was administered [5,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Article Highlightsmentioning
confidence: 99%
“…in this analysis) were treated with fosfomycin for osteomyelitis (acute or chronic, hematogenous, vertebral, post-traumatic, post-operative or in the presence of diabetic foot infectionlimb threatening osteomyelitis). Arthritis, pyogenic discitis, septic pseudoarthrosis, internal fixation infection and periprosthetic joint infections were some of the other indications for which intravenous fosfomycin was administered [5,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Article Highlightsmentioning
confidence: 99%
“…There is considerable clinical experience regarding the use of fosfomycin, mainly in combination regimens, for various types of bone infections [69], primarily complicated bone fractures [70] and osteomyelitis or septic arthritis in children [71,72]. It is noteworthy that a recent survey among paediatricians and paediatric orthopaedists in France found that the combination of fosfomycin with a third-generation cephalosporin was one of the most popular therapeutic options for acute osteomyelitis in children [73].…”
Section: Bone Infectionsmentioning
confidence: 99%